CAPACITY FACTOR BASED COST MODELS FOR BUILDINGS OF VARIOUS FUNCTIONS - Andreas Wibowo; Wahyu Wuryanti (Civil Engineering Dimension, 2007)
The desired accuracy level of an estimate heavily relies on the availability of data and information at the time of preparing the estimate. However, an estimate often must be made when data and information are not complete. At earlier stages of project implementation at which data and information are minimal, a client is often required to prepare a cost estimate. This paper discusses the capacity factor-based cost models for buildings with total areas serving as the proxy of capacity. A total of four cost models for different building functions are presented in this paper. Based on the models, most building functions with the exception of housings, exhibit decreasing return to scale, meaning that the unit measure of cost expressed by cost per square meter declines as the size of capacity increases. The cost models are then applied to estimate the development unit cost for different demographical unit measures.